Harmonisasi Sosial Masyarakat Perbatasan Indonesia-Malaysia - Suwartiningsih, Sri; Samiyono, David; Purnomo, Daru (Universitas Muhammadiyah Yogyakarta, 2018)
Indonesia is a country that symbolizes plurality. The horizontal conflicts caused by ethnicity, race, and religion show that there is a crisis of national integration and social disharmony within the country. Conflicts in several regions in Indonesia provoked by several things, namely, lack of empathy, tolerance, and trust. However, this is different from what was shown in the border communities in Kalimantan. The result of the research which was conducted in April to June 2015 showed that the people in Indonesia-Malaysia border (especially in districts Jagoi Babang) were able to respect one another in the context of national integration. Living side by side despite their different citizenship is the evidence that they have mutual interaction in many fields such as the economy, education, and health. This condition creates social harmony among those communities. The main reason is that they feel as one family (kinship) under Dayak Bidayuh descent. This sense of belonging is as the result of local wisdom which is still being conducted among them, called ritual Gawai.